Altered Neurophysiological Processing of Auditory Attention in Preschool Children With Sickle Cell Disease. (18th September 2017) - Downes, Michelle; Kirkham, Fenella J; Telfer, Paul T; de Haan, Michelle
Abstract: Objective: Sickle cell disease (SCD) is a genetic red blood cell disorder that often leads to stroke and executive dysfunction in school-age children and adults. This study aimed to characterize the development of the neural correlates of selective attention, an early component of executive function, in preschool children with SCD. Methods: Auditory event-related potentials (ERPs) were recorded while children attended to a story stream in one ear and ignored a second story in the other ear interchangeably. In total, 12 patients (mean age = 5.5, 7 males) and 22 typically developing children (mean age = 4.4, 10 males) were included in the final analyses. Results: By 100 ms, more positive ERP amplitudes were observed for attended relative to unattended stimuli in typically developing children but not those with SCD, suggesting deficits in the ability to focus attention. Reduced attention effects were associated with lower performance intellectual quotient Conclusion: There are deficits in early attention modulation in young children with SCD.